Metadata Management in Data Mesh: Toward Federated Discovery and Governance - Suguimoto, Rafael H.; Meirelles, Paulo; Braghetto, Kelly (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2025: Anais do XL Simpósio Brasileiro de Bancos de Dados, 2025)
Organizations striving for data-driven operations often encounter limitations with monolithic data architectures and centralized data teams, typically in terms of scalability and data governance. The Data Mesh paradigm has emerged as a promising, decentralized alternative, yet practical guidance for implementing its key components, particularly federated metadata management, remains limited. This paper systematically reviews academic contributions on metadata solutions in Data Mesh environments, analyzing architectural patterns, standards, and technologies. We investigate existing approaches, provide a detailed comparison, and pinpoint critical open challenges to enable scalable and interoperable metadata governance across domains.